Analisis Karbon Monoksida (CO) pada Udara Ambien di Pertigaan Y Simpang Rimbo Kota Jambi - Saragih, Guntar Marolop; Marhadi, Marhadi; Kalsum, Siti Umi; Tasniah, Nadila (Universitas Batanghari Jambi, 2025)
This research aims to determine the magnitude of the CO concentration in the ambient air at the Y T-junction Simpang Rimbo, Jambi City using a CO meter. Observations were carried out for 3 days (Sunday, Monday and Tuesday). Sundays and Mondays are held at 2 different times, namely the afternoon and evening. 1 day observation on Tuesday with 4 different times, namely Morning, Afternoon, Afternoon and Night. Each observation time at 1 point is carried out for 60 minutes. The results of the 3 day study showed that the highest CO concentration occurred on Tuesday during the day, namely 279,424.4 ??/??3, the lowest CO concentration occurred on Sunday at night, amounting to 63,426.27 ??/??3. Meanwhile, observations for 1 day on Tuesday showed that the highest CO concentration occurred in the afternoon at 9.0056 ??/??3. The CO concentration was higher when measuring for 3 days, this was due to the influence of time and the reduction in vehicles passing the observation point on Tuesday 6 February 2024.